Association of BMI and height with the risk of endometrial cancer, overall and by histological subtype: a population-based prospective cohort study in Japan. Issue 3 (May 2019) - Kawachi, Asuka; Shimazu, Taichi; Budhathoki, Sanjeev; Sawada, Norie; Yamaji, Taiki; Iwasaki, Motoki; Inoue, Manami; Tsugane, Shoichiro
Abstract : Evidence on the association between BMI, height, and endometrial cancer risk, including by subtypes, among Asian populations remains limited. We evaluated the impact of BMI and height on the risk of endometrial cancer, overall and by histological subtype. We prospectively investigated 53 651 Japanese women aged 40–69 years. With an average follow-up duration of 18.6 years, 180 newly diagnosed endometrial cancers were reported, including 119 type 1 and 21 type 2. The association between BMI, height, and endometrial cancer risk was assessed using a Cox proportional hazards regression model with adjustment for potential confounders. Overweight and obesity were associated positively with the risk of endometrial cancer. Compared with BMI of 23.0–24.9 kg/m 2, hazard ratios (HRs) (95% confidence intervals) were 1.93 (1.17–3.16) for BMI of 27.0–29.9 kg/m 2 and 2.37 (1.20–4.66) for BMI of at least 30.0 kg/m 2 . On analysis by histological subtype, with each increase in BMI of 5 U, the estimated HR of type 1 endometrial cancer increased (HR=1.54, 95% confidence interval: 1.21–1.98), but HR of type 2 endometrial cancer was unaffected. There was no statistically significant association between height and endometrial cancer risk. In conclusion, the risk of endometrial cancer was elevated in women with a BMI of at least 27.0 kg/m 2 . By histological subtype, BMI was associated with type 1, but not type 2 endometrial cancer risk among a population with a relatively low BMI compared with western populations. Abstract : Supplemental Digital Content is available in the text.